(untitled) (Agricultural Engineering, 2019)
The aim of the study was to carry out a research on the use of milking robots compared to utilization of milking parlors. There was no such study in literature on the milking farms in Poland and abroad. The presented study, except for scientific knowledge, provides also practical utilization as a good agriculture practice on the farm. Tests were carried out simultaneously in two barns belonging to the same farm. In barn K, milking was used in the rib bone milking parlor, and in barn N with milking robots. The results covering three years of research from 2016 to 2018 were presented. It was concluded that the milk yield of young cows in both barns was almost identical, while in the second and subsequent lactation, cows in barn N had higher yield. In barn N, about 3% more milk was obtained from LKS below 400 thaus. ml−1, compared to barn K. Time of cows’ utilization in both cowsheds was similar, while in barn N the life efficiency of culled cows was higher by about 1,000 kg of milk. The level of deficiency and its structure, due to the number and stage of lactation, were very similar in both barns. In barn N, the uniformity of milk production throughout the year was more even compared to barn K. There were reserves in the use of the milking robot due to the low number of cows per milking stand and the need to better adaptation of milking times to current cow performance. The milking robot improves cow welfare and ensures high milk yield and good cytological quality of milk.